2008
DOI: 10.1158/0008-5472.can-07-6017
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Overexpression in Prostate Cancer Linked to Purα Loss from a Novel Repressor Complex

Abstract: Increased androgen receptor (AR) expression and activity are pivotal for androgen-independent (AI) prostate cancer (PC) progression and resistance to androgen-deprivation therapy. We show that a novel transcriptional repressor complex that binds a specific sequence (repressor element) in the AR gene 5 ¶-untranslated region contains PurA and hnRNP-K. PurA expression, its nuclear localization, and its AR promoter association, as determined by chromatin immunoprecipitation analysis, were found to be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 39 publications
(61 reference statements)
3
53
0
Order By: Relevance
“…Significantly, it has been found that this suppressor protein(s) could be induced to re-express in AI cells through histone deacetylase inhibitors, such as trichostatin A, sodium butyrate or suberoylanilide hydroxamic acid (SAHA). Consequently, a normal AR function was restored as indicated by regaining an androgen-dependent phenotype and apoptotic sensitivity to chemotherapeutic agents (24)(25)(26)(27). Consistent with these findings, histone deacetylase inhibitors LAQ824 and SAHA have also been reported to repress AR at both the transcriptional and posttranslational levels (28,29).…”
Section: Downregulation Of Ar Expression By Peitc Through Epigenetic supporting
confidence: 54%
“…Significantly, it has been found that this suppressor protein(s) could be induced to re-express in AI cells through histone deacetylase inhibitors, such as trichostatin A, sodium butyrate or suberoylanilide hydroxamic acid (SAHA). Consequently, a normal AR function was restored as indicated by regaining an androgen-dependent phenotype and apoptotic sensitivity to chemotherapeutic agents (24)(25)(26)(27). Consistent with these findings, histone deacetylase inhibitors LAQ824 and SAHA have also been reported to repress AR at both the transcriptional and posttranslational levels (28,29).…”
Section: Downregulation Of Ar Expression By Peitc Through Epigenetic supporting
confidence: 54%
“…Whatever the mechanism involved, hnRNP K might play a role in the regulation of AR gene. Wang et al (2008) showed that in LNCaP cells 5 0 -untranslated region of the AR promoter harbours a suppressor element, which is directly bound hnRNP and Pura, but only the regulation of this latter is crucial for the repression of AR levels. Vice versa Shi et al (2008) have reported that transcriptional downregulation of AR in the aging rat liver and in oxidatively stressed hepatoma cells involve hnRNP K through the interactions with PARP-1 and the first may serve as a stabilising docking platform for the activating complex that governs AR stimulation; in this model, silencing of hnRNP K decreased AR expression.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, very little is known about the behaviour of hnRNP K in PCa; Nagano et al (2004) demonstrated that the hnRNP K was strongly overexpressed in PCa with respect to normal cell lines derived from the same patient and that the protein was differentially modulated in two cell lines by INF. More recently, Wang et al (2008) have shown that a novel transcriptional repressor complex containing Pura and hnRNP K binds the androgen receptor (AR) gene both in cell lines and in human prostate tissues. These results prompted us to better characterise the role of this protein in PCa.…”
mentioning
confidence: 99%
“…This suppression of the pur-α gene leads to attenuated pur-α downregulation of the hAR gene and contributes to increased AR expression (Wang et al 2008).…”
Section: Importance Of Regulatory Sequences In the Promoter And 5'utrmentioning
confidence: 99%